induction
play

Induction Stepwise induction (for T PA , T cons ) Complete - PowerPoint PPT Presentation

Induction Stepwise induction (for T PA , T cons ) Complete induction (for T PA , T cons ) 4. Induction Theoretically equivalent in power to stepwise induction, but sometimes produces more concise proof Well-founded induction


  1. Induction ◮ Stepwise induction (for T PA , T cons ) ◮ Complete induction (for T PA , T cons ) 4. Induction Theoretically equivalent in power to stepwise induction, but sometimes produces more concise proof ◮ Well-founded induction Generalized complete induction ◮ Structural induction Over logical formulae 4- 1 4- 2 Stepwise Induction (Peano Arithmetic T PA ) Example: Theory T + PA obtained from T PA by adding the axioms: Axiom schema (induction) ◮ ∀ x . x 0 = 1 (E0) F [0] ∧ . . . base case ◮ ∀ x , y . x y +1 = x y · x (E1) ( ∀ n . F [ n ] → F [ n + 1]) . . . inductive step ◮ ∀ x , z . exp 3 ( x , 0 , z ) = z (P0) → ∀ x . F [ x ] . . . conclusion ◮ ∀ x , y , z . exp 3 ( x , y + 1 , z ) = exp 3 ( x , y , x · z ) (P1) for Σ PA -formulae F [ x ] with one free variable x . To prove ∀ x . F [ x ], i.e., Prove that F [ x ] is T PA -valid for all x ∈ N , it suffices to show ∀ x , y . exp 3 ( x , y , 1) = x y ◮ base case: prove F [0] is T PA -valid. is T + ◮ inductive step: For arbitrary n ∈ N , PA -valid. assume inductive hypothesis, i.e., F [ n ] is T PA -valid, then prove the conclusion F [ n + 1] is T PA -valid. 4- 3 4- 4

  2. First attempt: Second attempt: Strengthening ∀ y [ ∀ x . exp 3 ( x , y , 1) = x y ] Strengthened property � �� � F [ y ] We chose induction on y . Why? ∀ x , y , z . exp 3 ( x , y , z ) = x y · z Base case: Implies the desired property (choose z = 1) F [0] : ∀ x . exp 3 ( x , 0 , 1) = x 0 ∀ x , y . exp 3 ( x , y , 1) = x y OK since exp 3 ( x , 0 , 1) = 1 (P0) and x 0 = 1 (E0). Again, induction on y Inductive step: Failure. ∀ y [ ∀ x , z . exp 3 ( x , y , z ) = x y · z ] For arbitrary n ∈ N , we cannot deduce � �� � F [ y ] F [ n + 1] : ∀ x . exp 3 ( x , n + 1 , 1) = x n +1 Base case: from the inductive hypothesis F [0] : ∀ x , z . exp 3 ( x , 0 , z ) = x 0 · z F [ n ] : ∀ x . exp 3 ( x , n , 1) = x n OK since exp 3 ( x , 0 , z ) = z (P0) and x 0 = 1 (E0). 4- 5 4- 6 Stepwise Induction (Lists T cons ) Inductive step: For arbitrary n ∈ N Assume inductive hypothesis Axiom schema (induction) F [ n ] : ∀ x , z . exp 3 ( x , n , z ) = x n · z (IH) ( ∀ atom u . F [ u ] ∧ . . . base case prove ( ∀ u , v . F [ v ] → F [cons( u , v )]) . . . inductive step F [ n + 1] : ∀ x , z ′ . exp 3 ( x , n + 1 , z ′ ) = x n +1 · z ′ → ∀ x . F [ x ] . . . conclusion ↑ for Σ cons -formulae F [ x ] with one free variable x . exp 3 ( x , n + 1 , z ′ ) = exp 3 ( x , n , x · z ′ ) (P1) To prove ∀ x . F [ x ], i.e., = x n · ( x · z ′ ) IH F [ n ] , z �→ x · z ′ F [ x ] is T cons -valid for all lists x , = x n +1 · z ′ it suffices to show (E1) ◮ base case: prove F [ u ] is T cons -valid for arbitrary atom u . ◮ inductive step: For arbitrary list v , assume inductive hypothesis, i.e., F [ v ] is T cons -valid, then prove the conclusion F [cons( u , v )] is T cons -valid for arbitrary atom u . 4- 7 4- 8

  3. Example Inductive step: For arbitrary lists u , v , Theory T + assume the inductive hypothesis cons obtained from T cons by adding the axioms for F [ v ] : flat ( v ) → rvs ( rvs ( v )) = v (IH) concatenating two lists, reverse a list, and decide if a list is flat (i.e., flat ( x ) is ⊤ iff every element of list x is an atom). Prove ◮ ∀ atom u . ∀ v . concat ( u , v ) = cons( u , v ) (C0) F [cons( u , v )] : flat (cons( u , v )) → ◮ ∀ u , v , x . concat (cons( u , v ) , x ) = cons( u , concat ( v , x )) (C1) rvs ( rvs (cons( u , v ))) = cons( u , v ) ( ∗ ) ◮ ∀ atom u . rvs ( u ) = u (R0) ◮ ∀ x , y . rvs ( concat ( x , y )) = concat ( rvs ( y ) , rvs ( x )) (R1) Case ¬ atom( u ) ◮ ∀ atom u . flat ( u ) (F0) ◮ ∀ u , v . flat (cons( u , v )) ↔ atom( u ) ∧ flat ( v ) (F1) flat (cons( u , v )) ⇔ atom( u ) ∧ flat ( v ) ⇔ ⊥ by (F1). ( ∗ ) holds since its antecedent is ⊥ . Prove ∀ x . flat ( x ) → rvs ( rvs ( x )) = x Case atom( u ) is T + flat (cons( u , v )) ⇔ atom( u ) ∧ flat ( v ) ⇔ flat ( v ) cons -valid. by (F1). Base case: For arbitrary atom u , rvs ( rvs (cons( u , v ))) = · · · = cons( u , v ). F [ u ] : flat ( u ) → rvs ( rvs ( u )) = u by R0. 4- 9 4- 10 Complete Induction (Peano Arithmetic T PA ) Is base case missing? No. Base case is implicit in the structure of complete induction. Axiom schema (complete induction) Note: ( ∀ n . ( ∀ n ′ . n ′ < n → F [ n ′ ]) → F [ n ]) . . . inductive step ◮ Complete induction is theoretically equivalent in power to → ∀ x . F [ x ] . . . conclusion stepwise induction. ◮ Complete induction sometimes yields more concise proofs. for Σ PA -formulae F [ x ] with one free variable x . To prove ∀ x . F [ x ], i.e., Example: Integer division quot (5 , 3) = 1 and rem (5 , 3) = 2 F [ x ] is T PA -valid for all x ∈ N , Theory T ∗ PA obtained from T PA by adding the axioms: it suffices to show ◮ ∀ x , y . x < y → quot ( x , y ) = 0 (Q0) ◮ inductive step: For arbitrary n ∈ N , ◮ ∀ x , y . y > 0 → quot ( x + y , y ) = quot ( x , y ) + 1 (Q1) assume inductive hypothesis, i.e., ◮ ∀ x , y . x < y → rem ( x , y ) = x (R0) F [ n ′ ] is T PA -valid for every n ′ ∈ N such that n ′ < n , ◮ ∀ x , y . y > 0 → rem ( x + y , y ) = rem ( x , y ) (R1) then prove Prove F [ n ] is T PA -valid. (1) ∀ x , y . y > 0 → rem ( x , y ) < y (2) ∀ x , y . y > 0 → x = y · quot ( x , y ) + rem ( x , y ) Best proved by complete induction. 4- 11 4- 12

  4. Well-founded Induction Proof of (1) ∀ x . ∀ y . y > 0 → rem ( x , y ) < y A binary predicate ≺ over a set S is a well-founded relation iff � �� � F [ x ] there does not exist an infinite decreasing sequence Consider an arbitrary natural number x . s 1 ≻ s 2 ≻ s 3 ≻ · · · Assume the inductive hypothesis Note: where s ≺ t iff t ≻ s ∀ x ′ . x ′ < x → ∀ y ′ . y ′ > 0 → rem ( x ′ , y ′ ) < y ′ (IH) � �� � F [ x ′ ] Examples: Prove F [ x ] : ∀ y . y > 0 → rem ( x , y ) < y . ◮ < is well-founded over the natural numbers. Let y be an arbitrary positive integer Any sequence of natural numbers decreasing according to < is Case x < y : finite: rem ( x , y ) = by (R0) x 1023 > 39 > 30 > 29 > 8 > 3 > 0. case y < ◮ < is not well-founded over the rationals. Case ¬ ( x < y ): 1 > 1 2 > 1 3 > 1 4 > · · · Then there is natural number n , n < x s.t. x = n + y is an infinite decreasing sequence. rem ( x , y ) = rem ( n + y , y ) x = n + y = rem ( n , y ) (R1) ◮ The strict sublist relation ≺ c is well-founded on the set of all IH ( x ′ �→ n , y ′ �→ y ) y < lists. since n < x and y > 0 4- 13 4- 14 Well-founded Induction Principle Lexicographic Relation For theory T and well-founded relation ≺ , Given pairs of sets and well-founded relations the axiom schema (well-founded induction) ( S 1 , ≺ 1 ) , . . . , ( S m , ≺ m ) ( ∀ n . ( ∀ n ′ . n ′ ≺ n → F [ n ′ ]) → F [ n ]) → ∀ x . F [ x ] Construct S = S 1 × . . . , S m for Σ-formulae F [ x ] with one free variable x. Define lexicographic relation ≺ over S as To prove ∀ x . F [ x ], i.e., F [ x ] is T -valid for every x ,   m i − 1 � � it suffices to show ( s 1 , . . . , s m ) ≺ ( t 1 , . . . , t m ) s j = t j ⇔  s i ≺ i t i ∧  ◮ inductive step: For arbitrary n , � �� � � �� � i =1 j =1 s t assume inductive hypothesis, i.e., F [ n ′ ] is T -valid for every n ′ , such that n ′ ≺ n for s i , t i ∈ S i . then prove • If ( S 1 , ≺ 1 ) , . . . , ( S m , ≺ m ) are well-founded relations, so is ( S , ≺ ). F [ n ] is T -valid. Complete induction in T PA is a specific instance of well-founded induction, where the well-founded relation ≺ is < . 4- 15 4- 16

Download Presentation
Download Policy: The content available on the website is offered to you 'AS IS' for your personal information and use only. It cannot be commercialized, licensed, or distributed on other websites without prior consent from the author. To download a presentation, simply click this link. If you encounter any difficulties during the download process, it's possible that the publisher has removed the file from their server.

Recommend


More recommend